Hypoparathyroidism and hypocalcaemia during treatment for acute leukaemia. Issue 6317 (6th March 1982) - Freedman, D B; Shannon, M; Dandona, P; Prentice, H G; Hoffbrand, A V
Abstract : Nine patients with acute leukaemia developed a complex syndrome of hypocalcaemia and hypomagnesaemia during treatment. These metabolic abnormalities developed rapidly in some patients and gave rise to acute symptoms. Immunoreactive parathormone concentrations in these patients were found to be either absolutely or inappropriately low. Hypomagnesaemia and the action of chemotherapeutic agents, especially adriamycin or cytarabine, or both may have contributed to the pathogenesis of this syndrome.